Development and characterization of microsatellite loci for the Moroccan endemic endangered species Argania spinosa (Sapotaceae)(1) - El Bahloul, Yasmina (Botanical Society of America, 2014)
• Premise of the study: Microsatellite loci were developed for the Moroccan endemic endangered species Argania spinosa with a combination of a typical library enrichment procedure and a 454 GS FLX Titanium–based high-throughput sequencing approach. • Methods and Results: A genomic DNA library was enriched and further screened using (GA)(15), (GTA)(8), and (TTC)(8) biotin-labeled probes coupled with chemi-luminescence detection. To increase simple sequence repeat (SSR) loci number, an ultra-high-throughput sequencing-based approach was used. Evaluation of all primer pairs was performed with labeled dUTP on an ABI 3130xl sequencer. Eleven polymorphic SSR loci were selected out of 79 SSR regions and extensively characterized on 150 individuals from eight populations. Total alleles ranged from six to 19 alleles per locus while expected heterozygosity ranged from 0.618 to 0.869. • Conclusions: The SSRs developed here will be used to further characterize the genetic diversity of A. spinosa across its distribution range, mainly in the southern part of Morocco and southwestern Algeria. They may also be transferable to other Sapotaceae species.